Vanadium, molybdenum and antimony contents in soils of different lithologies in Santa Catarina Teores de vanádio, molibdênio e antimùnio em solos de diferentes litologias em Santa Catarina - Suppi I.M.* (2021)
© 2021 Sociedade Brasileira de Quimica. All rights reserved.Trace element levels knowledge in soils is important for establishing quality standards. This study has objective to determine levels of vanadium (V), molybdenum (Mo) and antimony (Sb) in soils from Santa Catarina, observing the different source materials and establishing relationships between these elements and soil properties. The extractions occurred according to USEPA 3051 A protocol, with nitric and hydrochloric acid addition for V and Mo and only with hydrochloric acid for Sb. The quantification of V and Mo occurred by inductively coupled plasma optical emission spectrometry and of Sb by hydride generation inductively coupled plasma optical emission spectrometry. The results were submitted to variance analysis and Scott-Knott test and evaluated by Pearson's correlation with soil attributes. V and Mo contents differed between soils of different source materials. Highest V levels were found in andesite and basalt soils and Mo in porphyry phonolite, granite, mica schist and sedimentary rocks. V and Sb showed a positive correlation with each other and with oxides of iron, silt, and organic carbon. Mo showed a negative correlation with cation exchange capacity (CEC), iron oxides and organic carbon.